2019
DOI: 10.3390/cancers11071025
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib Promotes Dephosphorylation of NPM/B23 at Threonine 199 and Inhibits Endometrial Cancer Cell Growth

Abstract: Endometrial cancer incidence rates are growing, especially in countries with rapid socioeconomic transitions. Despite recent advances in chemotherapy, hormone therapy, and targeted therapy, advanced/recurrent disease remains a clinical challenge. Palbociclib—a selective inhibitor of cyclin-dependent kinases (CDK) 4/6—has therapeutic potential against estrogen receptor (ER)-positive and HER2-negative breast cancer. However, the question as to whether it can be clinically useful in endometrial cancer remains ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…The chemical inhibitors of CDK4/6, palbociclib, ribociclib and abemaciclib, have been used in multiple clinical trials worldwide to treat more than 30 different types of tumors, including endometrial cancer (38). A recent study demonstrated that increased expression of phosphorylated NPM/B23 (at Thr199) in cancer cells promotes its interaction with CDK6 and plays a key role in endometrial tumorigenesis (39). By inhibiting CDK4/6 kinase, palbociclib can inhibit the phosphorylation of NPM/B23 (Thr199) and promote the expression of estrogen receptor (ER)α, ultimately making hormone-refractory endometrial cancer sensitive to endocrine therapy (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical inhibitors of CDK4/6, palbociclib, ribociclib and abemaciclib, have been used in multiple clinical trials worldwide to treat more than 30 different types of tumors, including endometrial cancer (38). A recent study demonstrated that increased expression of phosphorylated NPM/B23 (at Thr199) in cancer cells promotes its interaction with CDK6 and plays a key role in endometrial tumorigenesis (39). By inhibiting CDK4/6 kinase, palbociclib can inhibit the phosphorylation of NPM/B23 (Thr199) and promote the expression of estrogen receptor (ER)α, ultimately making hormone-refractory endometrial cancer sensitive to endocrine therapy (39).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that increased expression of phosphorylated NPM/B23 (at Thr199) in cancer cells promotes its interaction with CDK6 and plays a key role in endometrial tumorigenesis (39). By inhibiting CDK4/6 kinase, palbociclib can inhibit the phosphorylation of NPM/B23 (Thr199) and promote the expression of estrogen receptor (ER)α, ultimately making hormone-refractory endometrial cancer sensitive to endocrine therapy (39). Yet, clinical trials of treatment with CDK9 inhibitors remain unsuccessful and involve many adverse effects (40).…”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed as previously described [ 29 ]. Briefly, 4-μm-thick FFPE PDX-mLung, primary DEC, and lung metastasis specimens were deparaffinized in xylene and rehydrated through a series of graded ethanol washes in water.…”
Section: Methodsmentioning
confidence: 99%
“…The Western blotting protocol was described in a previous study [34]. Briefly, cells were harvested, washed twice with PBS, and lysed in ice-cold RIPA lysis buffer.…”
Section: Western Blottingmentioning
confidence: 99%